Proyecto de factibilidad para la creación de una microempresa de productos de limpieza para la asociación de no videntes Dios con Nosotros de la provincia de Sucumbíos, cantón Lago Agrio, ciudad Nueva Loja - Labanda Jaramillo, Dixon Fabián (2015)
Our proposed intervention for Work Degree is to formulate project feasibility under the focus of the Popular and Solidarity Economy, taking into accounts the different components of production and marketing of cleaning products developed by the Association of Blind "God with us ". To do a market study where information was compiled to determine the unmet demand for the product, as well as different strategies on the marketing plan for the product was carried out; within the technical chapter, company size, factors such as location, organizational characteristics and other parameters that allow an efficient management of production and administrative processes was determined. Within the economic development study financial analysis of the company, where different costs and business expenses were projected to the respective financial statements that allowed to determine the financial viability of the planned business initiative; finally the environmental and social assessment where the environmental impact analysis to manage different chemicals for the manufacture of our products, where a responsible handling of these chemicals was determined focus, does not affect the environment nor to its inhabitants, provided finally with the intended purpose which is to generate cost-benefit of the association and improving their quality of life and their families.